A warmth-loving brother of northern siblings: the first subtropical species of Forinus Kurbatov discovered on Okinawa-jima, Japan (Coleoptera, Staphylinidae, Pselaphinae) - Jałoszyński, Paweł (Zootaxa, 2022)
To date, Forinus Kurbatov included only two species, known to occur in the Russian Far East: Primorye and Kunashir Island of the Kuril archipelago. Forinus mirus sp. n. is described, based on specimens collected on the subtropical island of Okinawa Island, Japan, 2,000 km south of the nearest previously known locality of this genus. Morphological structures of the new species are illustrated in detail and remarks on the primary diagnostic feature of the tribe Trichonychini, the sternite IX with the unpaired median penial plate, is discussed.